2020
DOI: 10.1002/cre2.364
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of salivary thioredoxin levels in oral lichen planus and oral squamous cell carcinoma

Abstract: Objective: Oral lichen planus (OLP) is a chronic mucocutaneous inflammatory disease, which is considered as a potentially malignant condition and could transformed into oral squamous cell carcinoma (OSCC). Squamous cell carcinmoma is the most common oral cancer. This study aimed to compare salivary thioredoxin levels as an antioxidant protein among patients with OSSC, OLP and healthy subjects.Materials and methods: Twenty-eight patients with OLP, 20 patients with OSCC and 40 healthy people enrolled in this obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In our study, we found that levels of thioredoxin 1 and peroxiredoxin 1 were downregulated in cancer as compared to those of leukoplakia and erythroplakia, respectively. A lower level of salivary TXN has also been reported in patients with ulcerative SCC compared to those with leukoplakia and erythroplakia [ 37 ]. Reduced levels of thioredoxin and other antioxidants react with ROS contributing to the characteristic increased levels of oxidative stress in cancer cells [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we found that levels of thioredoxin 1 and peroxiredoxin 1 were downregulated in cancer as compared to those of leukoplakia and erythroplakia, respectively. A lower level of salivary TXN has also been reported in patients with ulcerative SCC compared to those with leukoplakia and erythroplakia [ 37 ]. Reduced levels of thioredoxin and other antioxidants react with ROS contributing to the characteristic increased levels of oxidative stress in cancer cells [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…OLP is considered an inflammatory disease of the oral cavity mediated by immunity. However, it has been shown that 1.63% of OLP evolves into OSCC within 7 years and is therefore classified as a potentially malignant disease by WHO [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%